PHARMACOGNOSTICAL AND PHYTOCHEMICAL EVALUATION OF THE DRUG SAHADEVI (CYANTHILLIUM CINEREUM (L.) H. ROB.) (International Journal of Ayurveda and Pharma Research, 2019)
Sahadevi (Cyanthillium cinereum (L.) H.Rob.) (Family Asteraceae) commonly known as Purple Fleabane in English, Sahadei in Hindi and Poovankurunthila in Malayalam, an erect annual branched herb with pubescent cylindrical stem found as a weed throughout India is extensively used in folkore medicine. The present paper highlights the pharmacognostical and phytochemical characters of the plant to give clear standards for identification of the drug. Microscopic evaluation of root, stem and leaf as well powder microscopy of the plant were carried out. Physicochemical parameters like moisture content, total ash, water insoluble ash, acid insoluble ash, volatile oil content, sugar content, fibre content, alcohol soluble extractive and water soluble extractive were studied. Preliminary phytochemical analysis of the plant Sahadevi [Cyanthillium cinereum (L.) H.Rob.] showed the presence of steroid, flavonoid, glycoside, saponins and tannin. The present study signifies the use of TLC and HPTLC fingerprint profiles of aqueous and alcoholic extracts of the drug for determining the identity, purity of the drug and also for developing standards. The findings drawn from the study substantiates the genuineness of the drug Sahadevi [Cyanthillium cinereum (L.) H.Rob.], which is at par with the descriptions available in the authentic books.